2012
DOI: 10.1186/1746-6148-8-226
|View full text |Cite
|
Sign up to set email alerts
|

Assessing risk profiles for Salmonella serotypes in breeding pig operations in Portugal using a Bayesian hierarchical model

Abstract: BackgroundThe EU Regulation No 2160/2003 imposes a reduction in the prevalence of Salmonella in pigs. The efficiency of control programmes for Salmonella in pigs, reported among the EU Member States, varies and definitive eradication seems very difficult. Control measures currently recommended for Salmonella are not serotype-specific. Is it possible that the risk factors for different Salmonella serotypes are different? The aim of this study was to investigate potential risk factors for two groups of Salmonell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…A couple of research studies in Portugal found that the control of rodents was considered a protective factor for the presence of Salmonella serotypes other than S . typhimurium in pig farms (Correia‐Gomes and others , 2013), and this was also highlighted in other studies from Denmark (Skov and others ), the Netherlands (Meerburg and Kijlstra ), Spain (Vico and others ), and Brazil (Kich and others ). On the other hand, a study in Canada found no significant association between the presence of rodents and Salmonella infection status (Farzan and others ).…”
Section: Biosecuritysupporting
confidence: 60%
See 1 more Smart Citation
“…A couple of research studies in Portugal found that the control of rodents was considered a protective factor for the presence of Salmonella serotypes other than S . typhimurium in pig farms (Correia‐Gomes and others , 2013), and this was also highlighted in other studies from Denmark (Skov and others ), the Netherlands (Meerburg and Kijlstra ), Spain (Vico and others ), and Brazil (Kich and others ). On the other hand, a study in Canada found no significant association between the presence of rodents and Salmonella infection status (Farzan and others ).…”
Section: Biosecuritysupporting
confidence: 60%
“…One might think that the larger the herd, the greater the risk of introduction of contamination (Moore ) and risk could be associated with practices of mixing pigs, which may happen most frequently in larger herds. It has been considered that the larger the herd, the higher the risk of transmission given the higher number of “infectious” and “susceptible” animals, offering an increased chance of more effective contacts per unit of time (Correia‐Gomes and others ). The Natl.…”
Section: Biosecuritymentioning
confidence: 99%
“…Some locations and objects were more contaminated than others; they yielded more Salmonella isolates. Inside the barn, Salmonella was mostly isolated from the landing stage (14 isolates) (Fisher’s exact test; p<0.05) and to a lesser extent from the faeces (five samples on each farm yielded a total of 13 isolates), the mobile objects,5 the barn front door handle1 and the 100 cm section of the feed pipeline 1. The mobile objects are restricted to their respective farm and different Salmonella serotypes and lysotype were isolated indicating different origins.…”
Section: Resultsmentioning
confidence: 99%
“…Several risk factors for the transmission of Salmonella to pig have been well studied,5 including the role of rodents as vectors for Salmonella ,6 hygiene,7 8 lairage conditions,9 10 sources of animals,8 herd management,11 production system,12 feeds,13 antibiotics,14 parasite infestations15 and so on. However, none of these have focused on the comparative presence and dynamics of Salmonella on a network of farms interconnected within a common cooperative with shared common resources: piglets, feeds, swine transporters, a slaughterhouse, technicians and veterinarians.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factor studies help to determine which on farm actions may be most effective in reducing on farm prevalence as well as identifying factors likely to increase the risk of having Salmonella in the herd. A number of studies to identify such on-farm factors have been performed either using bacteriology (van der Wolf et al, 2001a ; Lo Fo Wong et al, 2004 ; García-Feliz et al, 2009 ; Correia-Gomes et al, 2012 , 2013 ), or serology (van der Wolf et al, 2001b ; Beloeil et al, 2007 ; Smith et al, 2010 ). Interestingly factors related to management such as all-in/all-out policy (AI/AO), hygiene, presence of other diseases such as Porcine respiratory and reproductive syndrome (PRRS) and particularly factors associated with feed (coarseness, meal vs. pelleted, home-produced vs. purchased) have been associated with infection, but results are not always consistent across studies, while findings on the effect of factors such as herd size, cleaning protocols, and antimicrobial usage are disputed.…”
Section: Introductionmentioning
confidence: 99%